2017
DOI: 10.1055/s-0043-104527
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy is safe and effective for pediatric patients with chronic pancreatitis

Abstract: Chronic pancreatitis is characterized by pancreatic inflammation and fibrosis, which eventually leads to the destruction of the pancreatic parenchyma and loss of both exocrine and endocrine function. Recent studies have estimated that the incidence of chronic pancreatitis in children is approximately 0.5 per 100 000 per year [1-3]. Despite this modest incidence rate, the disease burden of chronic pancreatitis in pediatric patients is substantial owing to the extreme disruption caused to the patients' childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…24 The safety and efficacy of P-ESWL have been demonstrated in numerous studies, but data for geriatric patients have not been previously reported. 1,14,15,27,29 Our study is the first to report the safety and efficacy of P-ESWL in geriatrics.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…24 The safety and efficacy of P-ESWL have been demonstrated in numerous studies, but data for geriatric patients have not been previously reported. 1,14,15,27,29 Our study is the first to report the safety and efficacy of P-ESWL in geriatrics.…”
Section: Discussionmentioning
confidence: 80%
“…P‐ESWL has been successfully applied in the treatment of pancreatic stones since 1987 and is now recommended as the first‐line therapy for young patients with uncomplicated painful CP and radiopaque stones ≥ 5 mm obstructing the MPD . The safety and efficacy of P‐ESWL have been demonstrated in numerous studies, but data for geriatric patients have not been previously reported . Our study is the first to report the safety and efficacy of P‐ESWL in geriatrics.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Once abdominal pain or other complications related to CP occurs, early treatment is indicated. Both endotherapy and surgery are effective for pancreatic stone clearance and pain relief, with complete stone clearance of > 80% [4] and complete pain relief of 77-91% [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…There are many optional treatments to remove pancreatic stones, such as ERCP, P-ESWL, mechanical lithotripsy, laser lithotripsy, surgery and others. [ 12 – 17 ] Among these methods, P-ESWL is a valid and minimally invasive treatment for pancreatic stones for its effectiveness and safety. [ 3 6 ] Although P-ESWL is a safe and effective therapeutic modality, complications happen now and then.…”
Section: Discussionmentioning
confidence: 99%